High Precision Identification Method for differential dq-lnductances of Permanent Magnet Synchronous Machines - Seilmeier, Markus; Ebersberger, Sebastian; Kellner, Sven; Piepenbreier, Bernhard; Reill, Josef (2010)
This paper presents a novel method to measure the dq-inductances of permanent magnet synchronous motors (PSM). Accurate knowledge of the machine parameters is very important for high precision field oriented control of PSMs. Additionally there is a trend towards sensorless control of this type of machine. Especially sensorless control with test signals is based on the differential inductances. However, the parameters vary during operation. On the one hand the inductances and the permanent magnet flux mainly depend on the load of the machine. On the other hand the stator resistance changes with temperature. As there actually exist methods to get the absolute dq-inductances this topic is kept short. The focus in this publication is set to the differential inductances.The authors propose a high frequency signal based method to analyse the load and frequency dependent differential inductances in the rotor reference frame with very high precision. The method was tested in the laboratory with different machines and brought reliable results.